Stereotip Dunia Ketiga dalam Film Bride and Prejudice - Inayatul Chusna (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2016)
Abstract The focus of this research is to expose the representation of the Third World (India) in a transnational film, Bride and Prejudice. By using the theory of representation and some concepts in postcolonial studies, the representation of the Third World are revealed through the characters of the First and Third World and their relationship. The representation of the Third World that creates center and peripheral, and the image of Center as everything confirm the stereotypical representation of the Third World. The love story of the film between the First and Third World characters actually creates prejudices which once again reflecting the First and Third World stereotypes. The genre of the film, the transnational genre, expected to give space for the Third World to be visualized equal cannot remove the stereotypical representation. Bride and Prejudice becomes a transnational film that presents colonial voices. Keywords: Postcolonialism, Representation, First and Third World, Stereotype. ——- Abstrak Fokus penelitian ini menjelaskan tentang representasi dunia ketiga (India) dalam sebuah film transnasional, Bride dan Prejudice. Dengan menggunakan teori representasi dan beberapa konsep kajian poskolonial, representasi dunia ketiga digambarkan melalui hubungan dunia pertama dan ketiga para tokoh film tersebut. Representasi dunia ketiga yang menyebabkan terjadinya pusat dan pinggiran, dan penggambaran pusat sebagai pengokohan stereotip representasi dunia ketiga. Cerita cinta dalam film tersebut, antara para tokoh dunia pertama dan ketigapada dasarnya menimbulkan praduga yang menggambarkan stereotipe dunia pertama dan ketiga. Genre film ini, genre transnasional, diharapkan dapat memberikan ruang bagi dunia ketiga mengenai kesetaraan tidak dapat menghapus stereotip terhadapnya. Bride dan Prejudice menjadi sebuah film transnasional yang merepresentasikan suara-suara kolonial. Katakunci: poskolonial, representasi, dunia pertama dan ketiga, stereotip.